Natural History and Prognostic Factors of Cholangiocarcinoma With Spinal Metastasis - Apiruk Sangsin (2018)
© Copyright 2018 The Author(s). Published by Wolters Kluwer Health, Inc. Study Design: This is a retrospective analysis. Objective: The aim of this study was to determine the epidemiology, survival, and prognostic factors for cholangiocarcinoma (CCA) with spinal metastasis. Summary of Background Data: CCA is an epithelial cell malignancy of the bile duct, and a frequent site for its metastasis is the spine. Many areas of Asia are endemic for CCAs. To date, there is limited data on the epidemiology, natural history, and prognostic factors of CCA with spinal metastasis, which is crucial for better management and treatment of the disease. Materials and Methods: Patients diagnosed with CCA were recruited to our study, in order to identify cases with spinal metastasis. The survival rate was estimated by the Kaplan-Meier method. The univariate and multivariate analyses of tumor-specific and spinal metastatic factors were performed to identify the independent factors that affect survival. Results: From 2006 to 2015, 4585 CCA patients were identified and 182 of these patients had spinal metastasis. The overall median survival of patients with spinal metastasis was 88 days. Serum carcinoembryonic antigen <5 ng/mL, carbohydrate antigen 19-9 <39 U/mL, albumin ≥3.5 g/L, and Frankel score D-E were found to be independent factors that resulted in better survival in a multivariate Cox regression analysis. CCA resection or spinal surgery did not prolong the survival of patients with spinal metastasis. Conclusion: Spinal surgery should be considered for CCA patients with spinal metastasis, who have a favorable prognosis, and are likely to live long enough to benefit from surgery. The aim is to palliate the symptoms and not as much to improve the survival.